Design and development of carnival game - Chan, Jun Xiang (Nanyang Technological University, 2020)
This project details the design and development of a pinball machine using electrical and electronic technology. The purpose of this project is to elevate the traditional carnival games by creating a portable pinball machine with Arduino technology and at the same time, contribute towards Science, Technology, Engineering and Mathematics (STEM) education.